Effect of cement mineralogy on the effectiveness of chloride-based accelerator. (October 2016) - Shanahan, Natallia; Sedaghat, Ahmadreza; Zayed, A.
Abstract: Chloride-based accelerators are widely used for non-reinforced concrete; however, their effectiveness varies when used with different cement types. The goal of this study was to investigate the effect of cement mineralogy on the accelerating efficiency of pure CaCl2 and commercial chloride-based accelerator. The accelerating efficiency was measured on three commercial cements (with similar C3 S content but variable mineralogy) in terms of heat flow and compressive strength development. Chlorides were determined to be less effective with high-C3 A/high-alkali cement. One of the cements with normal acceleration by chlorides was selected for doping with C3 A, sulfates and alkalis in order to reproduce the reduction in chloride performance. Alkalis, specifically K2 SO4, were determined to have a significant effect on chloride-based accelerator performance, whether pure CaCl2 or commercial admixture. Increasing C3 A or gypsum content alone did not appear to significantly affect acceleration, but in combination with high alkali content these phases can potentially reduce accelerator effectiveness.